Review of the Research on the Electricity-Carbon-Hydrogen Coupling Trading Market under the Energy Internet - JIANG Mingxuan, BIAN Yiheng, LI Gengfeng, HUANG Yuxiong, ZHANG Runfan (Dianli jianshe, 2025)
[Objective] In recent times，countries worldwide are actively promoting energy transition and low-carbon development，and the coupling of electricity，carbon，and hydrogen trading has become an inevitable trend in the development of China’s energy industry. However，the complexity of energy mutualization and information interaction across multiple systems is significantly enhanced introducing new challenges to the development of a coupled electricity-carbon-hydrogen trading market. [Methods] This study first introduced the existing research on the electricity-carbon and electricity-hydrogen markets and extensively analyzed the research methodology，coupling mechanism，trading mode，pricing，and clearing mechanism of the electricity-carbon-hydrogen market. Second，because of key challenges at both the physical and information levels that constrain market development，the a framework for the electricity-carbon-hydrogen coupling market within the Energy Internet was proposed to address these issues，along with its participa